VIBRATION OF ORTHOTROPIC CYLINDRICAL SHELL WITH A SET OF CUTOUTS AND INCLUSIONS OF ARBITRARY CONFIGURATION - Шопа, Тетяна Василівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the framework of the refined theory, which takes into account transverse shear deformation, the solution of the problem on the steady state vibrations of the orthotropic closed cylindrical shell with the arbitrary number of cutouts and rigid inclusions of the arbitrary geometrical form, orientation, and location is constructed. External boundaries of the shell are of the arbitrary geometrical configuration. Arbitrary harmonic in time boundary conditions are considered on the external boundaries of the shell and on the contours of the cutouts. The inclusions have different types of connections with the shell. The solution is built on the basis of the indirect boundary elements method and the sequential approach to the representation of the Green's function. The boundary value problem is reduced to the system of algebraic equations.